ANALISA PENGEMBANGAN SISTEM SYNCCHROMESH UNTUK PENINGKATAN EFISIENSI PADA KENDARAAN LISTRIK - Emir Ridwan; Fuad Zainuri; Danardono Danardono; M. Adhitya; Sonki Prasetya; Fachruddin Fachruddin; Asep Apriana; Dianta Mustofa Kamal (Politeknik Negeri Jakarta, 2018)
ABSTRACTThe transmission to be developed in this research a manual transmission type synchromesh which will be combined with the addition of replacement clutch in the form of cone. From the research of electric vehicles that have been carried out still retain the use of manual transmission for changing from conventional vehicles fuels oil by replacing the engine with a motor as a driver. This research was conducted to design synchromesh system on manual transmission which allows gearshift done without reduction of torque in one axis so as to produce gear shifting that does not experience slowing of vehicle to improve motor efficiency in electric vehicle. The mathematical model for the propulsion system is developed using the Matlab / Simulink software package, where the throttle engine angle and the power draw synchronously as a control signal to adjust the synchromesh in shifting then simulate, process and compare to obtain the effectiveness value of the control algorithm . The designs that have been made will be tested to obtain the optimal value of the transmission performance that has been designed. The simulation image of the development of the shift in the development manual transmission uses dynamic models of external and internal linkage, synchronization and drivetrain output.Keywords: transmission , efficiency, synchromesh, simulinkABSTRAKTransmisi yang akan dikembangkan pada penelitian ini adalah transmisi manual jenis synchromesh yang akan dikombinasikan dengan penambahan pengganti kopling berupa cone .Dari penelitian kendaraan listrik yang sudah dilakukan tetap mempertahankan penggunaan transmisi manual karena merubah dari kendaraan konvensional berbahan bakar minyak dengan menggantikan mesin dengan motor sebagai penggerak. Penelitian ini dilakukan untuk mendesain sistem synchromesh pada transmisi manual yang memungkinkan perpindahan gigi dilakukan tanpa pengurangan torsi di salah satu poros sehingga menghasilkan perpindahan gigi yang tidak mengalami perlambatan kendaraan untuk meningkatkan efisiensi motor pada kendaraan listrik. Model matematika untuk sistem propulsi dikembangkan dengan menggunakan paket perangkat lunak Matlab / Simulink , di mana sudut mesin throttle dan kekuatan menarik sinkron sebagai sinyal kontrol untuk mengatur synchromesh pada perilaku pergeseran, kemudian hasinya simulasi, diolah dan dibandingkan untuk mendapatkan nilai efektivitas algoritma control. Rancangan yang telah dibuat akan diuji untuk mendapatkan nilai optimal dari unjuk kerja transmisi yang telah dirancang .Gambaran simulasi pengembangan pergeseran pada transmisi manual pengembangannya menggunakan model dinamis dari eksternal dan internal linkage, sinkronisasi dan output drivetrain.Kata kunci : transmisi, efisiensi, synchromesh, simulink